Risk factors for loneliness: A literature review - Barjaková, Martina; Garnero, Andrea; d’Hombres, Béatrice (Social science & medicine (1982), 2023)
Increasingly, loneliness is being recognised as a serious problem with detrimental effects on health, as well as on social cohesion and community trust. To effectively tackle this complex issue, a clear understanding of the phenomenon and its main drivers is needed. Over years of scientific research on loneliness, many potential risk factors have emerged and been tested empirically. This narrative review of 109 studies provides a concise summary of empirical evidence on the main potential risk factors for loneliness and presents an additional section dedicated to the COVID-19 pandemic. Given the very large number of existing studies, emphasis is placed on recent meta-analyses and systematic literature reviews as well as longitudinal studies. Similarly, given the large number of possible risk factors for loneliness, which may differ based on the geographical and cultural context, this review focuses on studies from Europe and North America. The results show that demographic factors often correlate with loneliness, but in many cases the link becomes negligible when controlling for other factors. Often, physical and mental health problems are found to be associated with loneliness, and so are some psychological factors, such as neuroticism or extroversion. Loneliness also depends on the environment in which one lives, and possibly the broader socio-economic and socio-cultural contexts. Nevertheless, the review shows that ultimately everything comes down to the quantity and quality of social relationships. In particular, marital status, living arrangements and the characteristics of one's personal social network are quite consistently found to be among the strongest predictors of loneliness. These main findings about the risk factors for loneliness remained valid also during the COVID-19 pandemic. The findings of this review have implications for policy, as understanding who the most vulnerable groups are is key for designing targeted policy solutions that tackle loneliness. •A review of over one hundred articles examining risk factors for loneliness•Socio-demographic factors have mostly indirect links to loneliness•Social network characteristics and partner status matter the most for loneliness•Many risk factors for loneliness are interrelated and impact each other•Risk factors for loneliness remained roughly the same during the COVID-19 pandemic